Differentiation of Haemonchus placei from Haemonchus contortus by PCR and by morphometrics of adult parasites and third stage larvae - Santos, Michelle Cardoso dos [UNESP]; Vendrame Amarante, Monica Regina [UNESP]; Lucas da Silva, Maria Regina [UNESP]; Talamini do Amarante, Alessandro Francisco [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
Molecular and morphological methods were evaluated to distinguish between Haemonchus contortus and Haemonchus placei species. A total of 141 H. contortus and 89 H. placei male adult specimens collected from artificially infected lambs were identified individually by PCR analysis, using a species-specific primer pair. These PCR results were used as gold standard for Haemonchus spp. identification. Haemonchus placei presented higher mean spicule and barb lengths than H. contortus (P<0.05). However, some measurements overlapped. For this reason, a discriminate function did not allow the correct identification of 13 H. contortus and one H. placei specimen. The sheath tail length of the third stage larvae (L3), which comprises the distance between the tip of the larval tail and the end of the sheath tail, were measured. Only three of the 485 H. placei larvae (0.619%) had a sheath tail shorter than 85 mu m, while only four of the 500 H. contortus larvae (0.8%) presented a sheath tail longer than 85 mu m. The results indicated that 6.09% of the male adult specimens would be misclassified based on the discriminate function, while only 0.71% of infective larvae would be misclassified. Therefore, identification of L3 can be used as the first method to indicate the presence of H. placei and/or H. contortus in a population of domestic ruminants.

Métodos moleculares e morfológicos foram avaliados para a identificação de Haemonchus contortus e Haemonchus placei. No total, 141 H. contortus e 89 H. placei machos adultos, obtidos de cordeiros artificialmente infectados, foram identificados individualmente por PCR com o emprego de um par de “primers” espécie-específico. Esses resultados da análise por PCR foram considerados como padrão para a identificação das espécies de Haemonchus.Haemonchus placei apresentou valores médios de espículos e ganchos superiores aos de H. contortus (P<0,05). Entretanto, houve sobreposição de alguns valores. Por essa razão, a função discriminante não permitiu a identificação correta de 13 exemplares de H. contortus e de um, de H. placei. Foi medida a cauda da bainha de larvas infectantes (L3), que compreende a distância entre a ponta da cauda da larva e a ponta da cauda da bainha. Apenas três das 485 L3 de H. placei (0,619%) apresentaram a cauda da bainha com medida inferior a 85 µm e somente em quatro das 500 L3 de H. contortus (0,8%) essa medida foi superior a 85 µm. Os resultados demonstraram que 6,09% dos machos adultos seriam identificados erroneamente com base na função discriminante, enquanto a identificação incorreta de L3 seria de apenas 0,71%. Portanto, a identificação de L3 pode ser utilizada como método inicial para indicar a presença de H. placei e/ou H. contortus em uma população de ruminantes domésticos.
Keywords: Diagnosis; Trichostrongyloidea; Molecular biology; Ruminants; Epidemiology